The influence of traditional games and digital media on students' character values and social skills - Raihan Alfarobi; Ahmad Chaeroni; Muhamad Sazeli Rifki; Nuridin Widya Pranoto; Ilham Ilham (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examines the comparative effects of traditional games and digital media on the development of character values and social skills in elementary school physical education. Motivated by concerns regarding reduced social interaction due to the growing dominance of digital media, the study employed a mixed-methods design involving 69 fifth- and sixth-grade students in Padang, Indonesia. Students participated in interventions using traditional games (Gobak Sodor) and educational digital media (exergames). Data were collected through validated questionnaires and behavioral observation sheets, with quantitative analysis conducted using PLS-SEM and qualitative data analyzed thematically. The findings indicate that traditional games significantly improved students’ social skills, while digital media had a significant positive effect on character values. However, traditional games did not significantly influence character values, and digital media did not significantly affect social skills. These results show that each approach has selective strengths, suggesting that an integrated strategy combining cultural and technological elements may offer a more holistic physical education experience.